Statistics for the 21st century methodologies for applications of the future - Rao, C. Radhakrishna (Calyampudi Radhakrishna); Szekely, Gabor J. (Statistics, textbooks and monographs, 2000)
Presents a selection of articles presented at the Eighth Lukacs Symposium held at the Bowling Green State University, Ohio. This title discusses consistency and accuracy of the sequential bootstrap, hypothesis testing, geometry in multivariate analysis, the classical extreme value model, the analysis of cross-classified data, and econometrics.